A CASE REPORT OF THE USE TOCILIZUMAB IN REFRACTORY SYSTEMIC JUVENILE ARTHRITIS WITH PULMONARY INVOLVEMENT AND MACROPHAGE ACTIVATION SYNDROME - M. I. Kaleda; I. P. Nikishina; S. R. Rodionovskaya (Научно-практическая ревматология)
The paper describes a patient with refractory systemic juvenile arthritis treated with tocilizumab (TCZ). Specific features of therapeutic response in real clinical practice, aspects of individual TCZ safety in the development of macrophage activation syndrome and concurrent therapy are discussed.